Knowledge on Autism Spectrum Disorder in School Teachers at Government School of Pokhara - Acharya, Pooja; Baral, Prawesh (Janapriya Journal of Interdisciplinary Studies, 2023)
This research is entitled “Knowledge on Autism Spectrum Disorders in School Teacher at Government School of Pokhara”. The aim of the study is to assess the level of knowledge on Autism Spectrum Disorders (ASD) among school teachers of selected government schools and find out the association between selected demographic variables and level of knowledge on ASD. A descriptive cross sectional research design was used in eight government schools in Pokhara. A sample size of 114 was selected by complete enumeration sampling technique and data was collected through self -administrated structured questionnaire. Data was analyzed and interpreted using descriptive statistical methods such as frequency, percentage, mean and standard deviation. Chi square test was used to find out association between selected background variables and level of knowledge. The study revealed that 46.5 percent had medium level of knowledge, 43.9 percent had low level of knowledge and only few 9.6 percent had high level of knowledge. The mean score of teacher’s knowledge on ASD was 19.8772±5.0188 and range was 12-34. There was no statistically significant association between selected background variables and level of knowledge on ASD (P >0.05). The finding of the study concluded that less than ten percent of the respondent had high level of knowledge on ASD which means lack of knowledge on ASD among school teachers. Only one teacher had training on ASD. So, there is a need of formal training and awareness program on ASD to teachers for early identification of autistic problems and to enhance the children’s condition. This will help teachers to disseminate knowledge on ASD in communities as they are ‘broadcasting agents’ of social changes and development.